Synthesis of Submicron Hexagonal Plate-Type SnS2 and Band Gap-Tuned Sn1−xTixS2 Materials and Their Hydrogen Production Abilities on Methanol/Water Photosplitting - Kang Min Kim; Byeong Sub Kwak; Sora Kang; Misook Kang (International Journal of Photoenergy)
SnS2 and Sn1−xTixS2 (x = 0, 0.1, 0.3, 0.5, and 0.7 mol) materials were designed using solvothermal method with the aim to enhance hydrogen production from water/methanol water photosplitting. Scanning electron microscopy revealed hexagonal plates with one side, 3.0 μm in length, in the SnS2 materials. Pure SnS2 showed absorption band edges of above 660 nm, and the absorption was shifted to low wavelengths with the insertion of Ti ions. The evolution of H2 from MeOH/H2O (1 : 1) photosplitting over SnS2 hexagonal plates in the photocatalytic liquid system was 0.016 mL h−1 g−1, and the evolutions were enhanced in Sn1−xTixS2. In particular, 0.049 mL h−1 g−1 of H2 gas was produced in Sn0.7Ti0.3S2 without electrolytes and it increased significantly to more than 90.6% (0.47 mL h−1 g−1 evolutions) at higher pH using 0.1 M of KOH. Based on the UV-visible absorption spectra, the high photocatalytic activity of Sn1−xTixS2 was attributed to the existence of an appropriate band-gap state that retarded recombination between the electrons and holes.